2019
DOI: 10.5812/compreped.92316
|View full text |Cite
|
Sign up to set email alerts
|

General Anesthesia-Related Neurotoxicity: Status of Pediatric Surgeries at an Academic Hospital in the North of Iran

Abstract: Background: Recently, general anesthesia (GA)-related neurotoxicity has turned into a big concern. However, it seems that inadequate attention has been paid to the issue in Iran. Objectives: The aim of this survey was to investigate the frequency of elective surgeries in children under the age of three at an academic hospital in the north of Iran. Methods: This retrospective study was conducted at Alzahra Hospital affiliated to the Guilan University of Medical Sciences (GUMS). The records of all children who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In a survey from northern Iran, the incidence and some related factors of elective pediatric surgeries were evaluated. It was reported that urban boys underdoing circumcision were the most cases of elective surgeries before the age of three (21). In another study, knowledge, and practice of physicians at Guilan academic hospitals regarding GA-related neurotoxicity was evaluated, and it was revealed that the current curriculum should be revised (22).…”
Section: Discussionmentioning
confidence: 99%
“…In a survey from northern Iran, the incidence and some related factors of elective pediatric surgeries were evaluated. It was reported that urban boys underdoing circumcision were the most cases of elective surgeries before the age of three (21). In another study, knowledge, and practice of physicians at Guilan academic hospitals regarding GA-related neurotoxicity was evaluated, and it was revealed that the current curriculum should be revised (22).…”
Section: Discussionmentioning
confidence: 99%
“…Sevoflurane 2% with oxygen were as anesthesia maintenance. In spite of being aware from the potential risks of general anesthetic agents neurotoxicity in infants exception α2 agonists and opioids, we could not avoid them due to the type of surgery requiring deep anesthesia with a proper muscle relaxation (10,11). After confirming the proper depth of anesthesia, he underwent a laparotomy through a transverse left upper quadrant incision (Figure 2).…”
Section: Case Presentationmentioning
confidence: 99%
“…Spinal anesthesia (SA) is considered the choice of anesthesia for CS. Preventing the fetus from being exposed to anesthetic agents, early onset, and ease of performance are some advantages of this method compared to GA [5][6][7]. The risk of pulmonary aspiration, failed intubation, increased blood loss, higher degrees of postoperative pain, chronic pain, increased risk of postpartum depression, and oxygen toxicity are GA-related risks in CS [8][9][10].…”
Section: Introductionmentioning
confidence: 99%